Análise do assentamento funcional digital (AFD) sob a perspectiva arquivística e sua implantação no âmbito das IFES - Silva, Sandra Messa da (2019)
This research presents a study about the analysis of the Digital Personnel Files (AFD) from the archival perspective and its implementation in the context of the Federal Institutions of Higher Education – IFES. The objective of this research is to investigate the implementation of AFD, starting from the analysis of the norms determined by the Portaria Normativa / SEGRT number 4 (a normative instruction), published in March 10, 2016, emanated from the Ministry of Planning, which instituted AFD whithin the scope of the organs and entities of the Federal Public Administration's Civilian Staff System (SIPEC). The justification for this investigation is related to the result of the survey conducted in 2017, by the Observatory of Digital Documents, about the management and preservation of the digital archival documents of the IFES, that pointed the institutions don't consider as a priority the investment in the production, maintenance and access to the digital archival documents. An incipient scenery for the compliance of the normative instruction could thus be seen. For this study, a theoretical frame of reference has been incorporated to substantiate the objectives of the research, regarding the Cultural Patrimony, Documental Patrimony, Records and Digital Document, Diplomatic, Systemic Digital Preservation and Chain Custody. The contextualization of the study involves the files national policies, the IFES, the AFD project which is part of the Federal Government Personnel Management System (SIGEPE) and respective legislation. Therefore this research is an applied, quali-quantitative and exploratory one. The data collection was made through questionnaires addressed to the IFES, National Archives and MP, through the Electronic System of the Service of Information to the Citizen (e-SIC). In this study, it was found that the normative instruction /SEGRT/MP number 4, from the 10th of March, 2016, presents gaps and some inconsistencies, such as not informing which are the responsibilities of MP concerning the management, preservation and physical custody of the AFD documents, as well as the responsibilities of the IFES as producers, for the legal chain custody of those source of evidence documents. The referred normative instruction has been repealed by Regulatory Ordinance number 9, from the 1st of August, 2018 by the Personnel Management Department of MP, which also sets out the guidelines of the National Archive. Besides that, MP didn't submit documentation to prove the utilization of the Archival Document Management Digital System (SIGAD), nor the use of the Reliable Digital Archival Repository (RDC-Arq) for the management and preservation of the documents belonging to AFD. MP stated that the new SIGEPE-AFD implemented is an online database. Starting from the analysis and discussion of surveyed data it was possible to elaborate the guidelines to IFES, presenting alternatives for the production, preservation and access to archival documents which are source of evidence and generating sources of Digital Personnel Files. The transformation of the Business Systems used by IFES into Business SIGAD is among the recommendations presented, according to one of the scenarios of RDC-Arq used together with SIGAD, presented by the Electronic Documents Technical Chamber (CTDE), through the guideline number 3, published in November of 2015. The management of documents is an obligation of the Public Power and thus, the norms, recommendatios and guidelines issued by the National Council on Archives (CONARQ) and by the National Archive (AN) should be followed, as well as the Law number 8.159, published on January 8, 1991 and all the norms related to it.